Determinants of Sanitation and Menstrual Hygiene Adherence Among Female Students in Coastal North Sumatera Indonesia - Evi Naria; Indra Chahaya; Rusmalawaty Rusmalawaty; Novita Olivia Sinurat; Raihana Atika; Ardin Hermansyah Siagian (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Menstrual hygiene of women in coastal areas which do not fulfill the health standard can increase the risk of reproductive tract infections, such as vaginal discharge, candidiasis, fungal infections, and cervical cancer. Limited access to sanitation facilities, lack of information, and poor hygiene habits negatively affect menstrual hygiene practices Objective : to analyze predisposing, reinforcing, and enabling factors related to menstrual hygiene among female students in coastal areas Research Methods/ Implementation Methods : This research was an observational study with a crosssectional design conducted in Medan City and Batubara Regency. The sample consisted of 300 female junior high school students who had experienced menstruation. Variables included age at menarche, sources of information, and knowledge of menstrual hygiene (Predisposing), family support and menstrual restrictions (Reinforcing), availability of clean water, soap, and dustbins (Enabling). Data were analyzed using cross-tabulation and the Chi-square test with a 95% confidence interval. Results : The results showed that 56% had their first menstruation (menarche) after the age of 12, 94.3% received information from their families, and 52% had good knowledge, all significantly related to menstrual hygiene practices (p = 0.005). Family support was also significantly associated (p = 0.014). Despite the availability of clean water (93.7%), soap (81.7%), and dustbins (81.7%), poor menstrual hygiene was still found in 86.7% of the students Conclusion/Lesson Learned : Knowledge, as a predisposing factor, and family support, as a reinforcing factor, need to be improved to improve the sanitation and menstrual hygiene practice